Implementation of Dialogic Communication on The Kodiklatal Website - Sudarsono, Meryana Deasy Karina; Kriyantono, Rachmat; Sujoko, Anang (Syntax Literate, 2024)
Ease of obtaining information within the government environment is highly recommended in order to realize good governance. Websites play an important role in becoming a new communication pattern between the government and the public which is considered easier and more appreciative. This research aims to prove how Kent and Taylor apply the principles of Dialogic Communication on the website of the Indonesian Navy's Doctrine Development, Education and Training Command (Kodiklatal). This research uses a positivistic paradigm and quantitative methods which aim to reveal scientific explanations about cause-and-effect relationships. The overall analysis results show that the implementation of the Dialogic Communication principles on the Kodiklatal website is fairly good with a total percentage of 60%. The Kodiklatal website has provided facilities for its visitors to interact with the organization. From the research results, it can be concluded that the Kodiklatal website applies the principles of Dialogic Communication well and is acceptable to the public.